[4]‐Cyclo‐2, 7‐Carbazole as Host Material in High‐Efficiency Phosphorescent OLEDs: A New Perspective for Nanohoops in Organic Electronics. Issue 3 (29th November 2022) - Brouillac, Clément; Lucas, Fabien; Tondelier, Denis; Rault‐Berthelot, Joëlle; Lebreton, Christophe; Jacques, Emmanuel; Quinton, Cassandre; Poriel, Cyril
Abstract: In the last ten years, the development of π‐conjugated nanohoops has been considerable owing to their remarkable properties. However, to date, their incorporation in organic electronic devices remains very scarce. In this work, the first high‐performance organic electronic device (i.e., phosphorescent organic light‐emitting diode, PhOLED) incorporating a nanohoop ([4]‐cyclo‐ N‐ butyl‐2, 7‐carbazole, [4]C‐Bu‐Cbz ) is reported, revealing the potential of nanohoops in electronics. Thus, using the red phosphor Ir(MDQ)2 (acac), the [4]C‐Bu‐Cbz ‐based PhOLED displays a high external quantum efficiency (EQE) of 17.0%, a current efficiency (CE) of 20.6 cd A −1 and a power efficiency (PE) of 25.8 lm W −1 demonstrating that the charge injection, transport, and recombination are particularly efficient. This performance is significantly higher than that of its linear counterpart, N ‐butyl‐2, 7‐quartercarbazole ([4]L‐Bu‐Cbz ), which presents an EQE of 11.1%, a CE of 13.0 cd A −1 and a PE of 15.7 lm W −1 . The significant difference, in terms of device performance, between cyclic and acyclic compounds provides a new basis to construct high‐performance electronic devices. This study, which includes optical, electrochemical, morphological, and charge transport properties, shows that nanohoops can be efficiently used as organic semiconductors in electronics and opens the way to their practical uses in high‐performance optoelectronic devices, which is now the next stage of their evolution. Abstract : A high‐performance phosphorescent organic light‐emitting diode incorporating a nanohoop is reported, revealing the potential of this family of π‐conjugated systems in electronics. The significant difference, in terms of device performance, between cyclic and acyclic compounds is discussed providing a new basis to construct high‐performance electronic devices.